Effect of P over the yielding and extraction of NP of cultivated bean in three soils. - García, Aurelio (2016)
Under controlled conditions and utilizing three soils of Red Ferralithic (Eutric Ferrasols) type with low, medium and high available P we studied the effect over the production of dry matter and the extraction of N and P performed by the bean plant (Phaseolus vulgaris L.), produced by the addition in increasing dosage of P, between 0 and 280 kg P2O5/ha, with fixed basis of 60 kg K2O/ha and 40kg N/ha and inoculation with bacteria from the Rhizobium genera. The experimental results showed a plant response differentiated by the availability of P in the soil. In soils with low P contents there was a positive response in the three evaluated indexes, while in the other two soil samples the higher availability of P produced a smaller or negative response. We also discuss the functional relationship found among the evaluated indexes.